Strategic Management of the Regional Economic Security in the Digital Economy - KARSUNTSEVA, Olga Vladimirovna; DENISOVA, Olga Nikolaevna; BURKINA, Tatiana Alexandrovna (Journal of Advanced Research in Law and Economics, 2019)
The approaches to understanding the concept of ‘economic security of a region’ have been systemized in the article; the terms have been extended due to the introduction of the concept of ‘economic security of a digital infrastructure of a region’, and the modern innovative mechanisms for ensuring the economic security of a region in the context of digital transformation have also been summarized. The most typical threats to economic security for the regions of the Volga Federal District of the Russian Federation in the context of digitalization have been highlighted in the article. The conclusion has been made about the economic security goals of the region, which directly depend on the regional characteristics of the use of digital technologies and the long-term needs of society.